2017
DOI: 10.3390/ijms18061106
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of CD26+ Cancer Stem Cells with Metastatic Properties in Colorectal Carcinogenesis

Abstract: Colorectal cancer results from genetic aberrations which accumulate over a long period of time, with malignant and metastatic properties acquired at a relatively late stage. A subpopulation of CD26+ colorectal cancer stem cells are known to be implicated in metastasis. We quantified CD26+ cancer cells in 11 primary tumor samples by flow cytometry, and showed that tumors having confirmed or suspected metastases harbored a relatively high CD26+ level in these samples. We hypothesized that this subpopulation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…This study suggests that the analysis of CSC subsets in the primary colon cancers according to CD26 expression may have important clinical implications as a selection criterion for adjuvant therapy. CD26 expression in colorectal cancers is observed particularly at late stages of tumor development and implies the emergence of a tumor cell population endowed with metastatic potential [ 383 ]. The CD26 + tumor cell population is maintained by genetic alterations at the level of TP53 and PIK3CA [ 383 ].…”
Section: Colon Cancer Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study suggests that the analysis of CSC subsets in the primary colon cancers according to CD26 expression may have important clinical implications as a selection criterion for adjuvant therapy. CD26 expression in colorectal cancers is observed particularly at late stages of tumor development and implies the emergence of a tumor cell population endowed with metastatic potential [ 383 ]. The CD26 + tumor cell population is maintained by genetic alterations at the level of TP53 and PIK3CA [ 383 ].…”
Section: Colon Cancer Stem Cellsmentioning
confidence: 99%
“…CD26 expression in colorectal cancers is observed particularly at late stages of tumor development and implies the emergence of a tumor cell population endowed with metastatic potential [ 383 ]. The CD26 + tumor cell population is maintained by genetic alterations at the level of TP53 and PIK3CA [ 383 ]. In vitro studies have shown the generation of CD26 + cells from CD26 − cells [ 383 ].…”
Section: Colon Cancer Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deamination to inosine is mediated by ADA, an enzyme generally present in the cytoplasm but that can be localized on the cell surface when bound to anchoring proteins, such as CD26 [ 62 ]. CD26 plays a significant role in CLL biology, being both a disease marker and a modifier of tumor pathogenesis and development [ 63 , 64 , 65 , 66 ]. Several studies highlighted that expression of CD26 identifies CLL patients with high-risk of disease progression and treatment requirement [ 67 ].…”
Section: Expression Of the Adenosinergic Axis Machinery On Cll Celmentioning
confidence: 99%
“…The aim of this study was to test candidate CSC and MetSC markers in a panel of eight cell lines obtained from primary or metastatic tumors of patients in different disease stages [so that epithelial-mesenchymal transition (EMT) markers were also used]. The results would provide a functional characterization of specific cell subsets found in clinical specimens (Lieto et al, 2015; Cheung et al, 2017) and the possibility of using these chemo-resistant cells as targets for the development of new therapies.…”
Section: Introductionmentioning
confidence: 99%